Resistance reduction through air layer formation beneath a vessel - Jaafar, Fatimah Amirah (2015)
Air bubble lubrication system is one of the techniques for ship energy saving in lowering ship frictional resistance. Air lubrication technique can reduce the skin friction using air layer or artificial air cavity generated beneath a vessel by air injection. This research presents the study on resistance reduction on a displacement hull model with microbubble generated beneath the vessel. Microbubble barriers were made in order to trap the generated microbubble more effectively beneath the vessel model. The subject of the study was a tanker model (MTL 036) with main dimension: L = 2.956 m, B = 0.436 m and T = 0.174 m. Resistance test was carried out at Marine Technology Centre, Universiti Teknologi Malaysia. The experiment conducted in two different conditions: resistance test without microbubble and resistance test with microbubble. The model was towed using the towing carriage and the resistance force (x-axis) and side force (y-axis) were recorded from 0.704 m/s to 1.14 m/s (equivalent to 10 knots to 16 knots in full scale). The model test results show that the total resistance with microbubble is lowered by 6 % to 13.9 % at the speed of 0.704 m/s and 0.849 m/s. The rate of resistance reduction decreases when the speed of the model increases. The highest resistance reduction was obtained at the speed of 0.849 m/s where 13.9 % reduction in resistance is achieved. The micro-bubble barriers are found to be able to effectively trapped the air beneath the model and reduce the total resistance effectively